Guideline for Financial Transactions Services through Mobile Banking of Bank of Ayudhya Public Company Limited - Kanungkid, Kittipong; Bangkerd, Santhanee (Journal of Industrial Business Administration, 2020)
This study aims to study guideline for financial transactions services through mobile banking of Bank of Ayudhya Public Company Limited in Rayong. This is done by considering demographic, marketing mix, innovation and technology acceptance, and information system quality. To compare use of financial transaction services according to demographic, samples are 100 financial transactions services users. The data is collected by questionnaires. The statistic is analyzed by percentage, mean, S.D., significant level, t-test, and ANOVA,. From the study, most of financial transaction services users are male who are 20-35 years old and obtain a bachelor degree. They work for private companies and the average income is 15,000-35,000 THB/month. Overall of the guidelines for financial services is high. Overall prioritizing of marketing mix, innovation and technology acceptance, and information system quality, and use of financial transaction services is high. Individually, it is highly in intelligible information, various functions i.e. payment service and the change of transaction can be tracked real-time by mobiles and transfer. There is no difference in the comparison of guidelines for using financial transaction services prioritizing mean in the edge, occupation, and monthly income at a significant level of .05. However, gender and the educational degree are different at the significant level of .05.